The responsible behavior of tourist: The role of personnel factors and public power and effect on the choice of destination - Samar Zgolli; Imed Zaiem (Arab Economic and Business Journal, 2018)
The purpose of this study is to examine the effect of social engagement, the concern for sustainable tourism, the exemplarity of public power on responsible behaviour of tourist, and the effect of the responsible behaviour on the choice destination. A 544 questionnaires were completed and structural equation modeling with AMOS was used to test the hypothesis. The findings highlight a positive effect of the determinants studied on responsible behavior of the tourist. It is only the concern with sustainable tourism what has no significant effect on the responsible behavior. Otherwise, the effect of responsible behavior of tourist on the choice of destination is positive.
Keywords: 650; Sustainable tourism; Tourist's responsible behavior; Destination's choice; Social engagement